Assessing multimodal spoken word-in-sentence recognition in children with normal hearing and children with cochlear implants - Holt, Rachael Frush (2010)
PURPOSE: To examine multimodal spoken word-in-sentence recognition in children. METHOD: Two experiments were undertaken. In Experiment I, the youngest age with which the multimodal sentence recognition materials could be used was evaluated. In Experiment II, lexical difficulty and presentation modality effects were examined, along with test-retest reliability and validity in normal-hearing children and those with cochlear implants. RESULTS: Normal-hearing children as young as 3.25 years and those with cochlear implants just under 4 years who have used their device for at least 1 year were able to complete the multimodal sentence testing. Both groups identified lexically easy words in sentences more accurately than lexically hard words across modalities, although the largest effects occurred in the auditory-only modality. Both groups displayed audiovisual integration with the highest scores achieved in the audiovisual modality, followed sequentially by auditory-only and visual-only modalities. Recognition of words in sentences was correlated with recognition of words in isolation. Preliminary results suggest fair to good test-retest reliability. CONCLUSIONS: The results suggest that children’s audiovisual word-in-sentence recognition can be assessed using the materials developed for this investigation. With further development, the materials hold promise for becoming a test of multimodal sentence recognition for children with hearing loss.